Desain Pembelajaran Bangun Ruang Sisi Lengkung Bola Menggunakan PMRI Berbantuan Adobe Animate - Kholidatul Muna; Sudargo Sudargo; Agnita Siska Pramasdyahsari; Farida Nursyahidah (Departement of Mathematics Education, 2024)
Understanding the concept of geometric figures on the curved side of a sphere is an important subject for students in learning mathematics. However, students had difficulties when they were learning about geometric shapes on the curved side of a sphere. This research aimed to createta learning pathway which supports students in understanding the concept of the curved side of a ball through applying the context of Mitoni tradition inlclass IX of junior high school. The research subjects involved students at SMP N 39 Semarang, consisting of 33 students. The method applied was a validation research type design, where consists of three stages; they are initial design, design experiments (pilot experiments and teaching experiments), and retrospective analysis. The arrangement of learning activities was designed and developed based on the PMRI approach with the help of Adobe Animate. The results of this research were three activities involving: observing videos of the Mitoni tradition to identify the characteristics of the sphere; determine the formula for the surface area of a sphere; determine the ball volume formula; as well as solving contextual problems relatedtto sphere. Through the activities carried out, students can increase their understanding oftthe concept of geometric shapes on the curved side of a sphere in class IX of SMP N 39 Semarang. Apart from that, it can increase local cultural alternatives which can be used as context intthe mathematics learning process,respecially in material on the curved side of a sphere.